A Research about Mathematical Visualization Perceptions of Mathematics Teacher Candidates in Terms of Some Variables - İlhan, Aziz; Tutak, Tayfun (My University, 2021)
This study was conducted to examine mathematical visualization perceptions of mathematics teacher candidates in terms of gender, grade level, and parental educational status. Survey model was used. The population of the research consisted of mathematics teacher candidates who studied at the faculty of education of a university in the Southeastern Anatolia part of Turkey. The sample of the study consisted of 231 mathematics teacher candidates (159 Female, 72 Male) chosen by simple random sampling method from this population. In the study, Mathematical Visualization Perception Scale was used for getting data. The data were analyzed using SPSS. The descriptive analysis, study variable; average, percentage, and standard deviation were used. In addition, unpaired t-test for analyzing variation about gender variable, ANOVA, and LSD tests were preferred for analyzing variation about grade level and parental education status. As a result of the study findings, it was determined that the level of mathematical visualization perceptions of mathematics teacher candidates was no significant difference in terms of gender, but it was a significant difference in terms of grade level. Furthermore, math visualization perception level significantly differed according to parental education status.
Keywords: Mathematics education; Mathematical visualization perception; mathematics teacher candidates